From Institutional Authority to Digital Actors: The Transformation of Interfaith Dialogue in the Digital Technology Era - Philips, Gerardette (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
The rapid development of digital technology has fundamentally transformed the landscape of interfaith dialogue, reshaping not only patterns of communication among religious communities but also the distribution of religious authority and the formation of religious public spheres. This study aims to systematically examine how digital transformation—through social media, artificial intelligence, and online ecosystems—reconfigures the practices, actors, and meanings of interfaith dialogue in the contemporary era. This research is particularly significant given the growing role of digital technology as both a medium and a mediating structure of religious dialogue, which generates new opportunities while simultaneously raising complex ethical, epistemological, and theological challenges. This study adopts a qualitative approach through the Systematic Literature Review (SLR) method by examining journal articles, conference proceedings, and academic books published between 2020 and 2024 and sourced from reputable international databases. The analysis follows stages of systematic selection, thematic coding, and conceptual synthesis to identify major patterns of findings, shifts in authority, and theoretical tendencies within the scholarship on digital interfaith dialogue. The findings indicate that digital platforms significantly expand the space for interfaith dialogue by enhancing inclusivity, accessibility, and participation across geographical and institutional boundaries. At the same time, this transformation accompanies a shift in religious authority from institutional structures toward decentralized digital actors, including religious content creators and artificial intelligence–based systems that function as epistemic mediators. On the other hand, the study also reveals serious challenges, such as algorithmic bias, disinformation, the commodification of religious practices, and increasing dependence on AI-based dialogue systems, all of which risk reducing the depth of theological reflection and the overall quality of interfaith engagement. The implications of this study underscore the urgency of developing a prophetic and theological approach as a normative framework for responding to digital transformation. Such an approach positions religious communities as critical actors in shaping digital ethics, strengthening technological literacy, and fostering cross-sector collaboration with technology stakeholders. The originality of this study lies in its critical synthesis that integrates interfaith dialogue studies, digital religion, and artificial intelligence within a single analytical framework, thereby enriching the conceptual understanding of religious studies amid global digital transformation.